025 The safety of etriage to provide advice rather than face-to-face neurology appointment. Issue 12 (14th November 2019) - Bennett, Karina; Boisanger, Louis de; Moreton, Fiona; Davenport, Richard; Stone, Jon
Abstract : The number of neurology referrals in Scotland has increased inexorably. Active triaging of primary care referrals is a method of controlling this demand and it is apparent that not all primary care referrals need to be seen in an outpatient clinic, some can reasonably be dealt with 'advice only'. The aim was to review the safety and cost-effectiveness of offering 'advice only' rather than outpatient appointments for neurology patients in NHS Lothian. GP referrals triaged by a neurology consultant as 'advice only' were identified over a 6-month period. Data was collected on reason for referral, opinion of triaging neurologist and whether the patient re-presented to secondary services within a 12-month period with the same symptoms. 236 patients were given advice only. 70% (n=166) patients had no further secondary care presentations in 12-months. The most common presentation was headache (n=57, 13%). 1 patient had a major diagnostic change following delayed review. Offering advice prevented unnecessary appointments which would not have changed management, was safe and likely to be cost-effective. Use of 'advice only' response allows resources to be redirected to seeing more medically appropriate consultations.